2020
DOI: 10.1111/scs.12863
|View full text |Cite
|
Sign up to set email alerts
|

A ‘near‐life experience’: lived experiences of spirituality from the perspective of people who have been subject to inpatient psychiatric care

Abstract: Aims To describe lived experiences of spirituality from the perspective of people who have been subject to inpatient psychiatric care and to interpret these experiences from an understanding of health as dialectical. Methods After approval from a regional ethical board, eleven participants were recruited from two organisations for people with mental health problems. Participants were asked to narrate about spiritual experiences and occasions where such experiences had come close. The transcribed interviews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Health care staff in mental health hospitals who are working with very ill patients have an ethical and professional duty to develop knowledge, skills, and attitudes to assess and address their patients also in the area of spirituality; this domain is an aspect of whole person patient-centered care (Saleem et al, 2014;Medås et al, 2017;Patterson et al, 2018). In discerning how to assess patients spiritually, Koslander et al's (2020) advises mental health nurses that spirituality can be both a resource and a challenge and is worth noticing, acknowledging, and discussing among the healthcare team members. In a Scandinavian context, it might also be helpful to try to determine if patients have a restful religiosity that is deeply integrated into the person and thus might provide support in times of illness, or if there is some conflict related to their belief system.…”
Section: Educational Preparation For Spiritual Carementioning
confidence: 99%
See 2 more Smart Citations
“…Health care staff in mental health hospitals who are working with very ill patients have an ethical and professional duty to develop knowledge, skills, and attitudes to assess and address their patients also in the area of spirituality; this domain is an aspect of whole person patient-centered care (Saleem et al, 2014;Medås et al, 2017;Patterson et al, 2018). In discerning how to assess patients spiritually, Koslander et al's (2020) advises mental health nurses that spirituality can be both a resource and a challenge and is worth noticing, acknowledging, and discussing among the healthcare team members. In a Scandinavian context, it might also be helpful to try to determine if patients have a restful religiosity that is deeply integrated into the person and thus might provide support in times of illness, or if there is some conflict related to their belief system.…”
Section: Educational Preparation For Spiritual Carementioning
confidence: 99%
“…Hvidt et al (2017) ask the question if crisis religiosity has become the predominant form of religious expression in the Scandinavian population. Koslander et al (2020), also reporting from Scandinavia, found that patients who had been inpatient in psychiatric care described their experiences of spiritually as going beyond religion, even though religious experiences were part of it. Spirituality could provide resources such as hope, connectedness, meaning, and coherence in life, but also give rise to doubt, anxiety and feelings of loneliness, and hopelessness.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…These beliefs include their meaning given to life, sense of hope, and faith. Consequently, the person may experience a sense of doubt, confusion, and tension (Kord & Biadar, 2019 ; Koslander et al, 2021 ; Mrdjenovich, 2019 ). Concepts such as religious struggle, spiritual stress, and religious anguish thus found their way into health care providers' literature.…”
Section: Introductionmentioning
confidence: 99%